Cultura ed educazione nel secondo dopoguerra. L'esempio de «Il Politecnico» - Giovambattista Trebisacce (Firenze University Press, 2020)
This article intends to propose a pedagogical reading of Italian culture post-WWII period, through the usage of the Marxist categories "ideology" and "praxis". The Italian Resistance, a demotic movement aimed at building the new Italy from scratch, is a clear example of "praxis pedagogy", in which theory and practice coexhist, fulfilling one another. The end of the Resistance's spirit and the beginning of a national Reconstruction policy produce the return to old values, bringing out an ideological, conformistic and adaptive pedagogy, of which the stance of Vittorini's magazine "Il Politecnico" and the largest part of the Italian cultural environment of the time are the most significant example.